Immunolocalization of protein-bound 3-nitrotyrosine in inflammatory myopathies - Zámečník, Josef; Vytášek, Richard; Vencovský, Jiří; Vilím, Vladimír (Česko-slovenská patologie a Soudní lékařství, 2011)
3-nitrotyrosine (3NT) is regarded as a “footprint” of nitric oxide generation. The study aimed at documenting the presence and distribution of 3-nitrotyrosine (3NT) in muscle tissue samples from patients with idiopathic inflammatory myopathies (IIM) as well as from those with non-inflammatory myopathies to consider whether polymyositis (PM) and dermatomyositis (DM) could be distinguished based on 3NT immunohistochemistry in muscle biopsy. Cryosections prepared from muscle biopsies of 54 patients with either IIM, i.e. PM and DM, or various non-inflammatory myopathies were immunostained using monoclonal antibody against 3NT. The 3NT immunostaining was localized to endothelial cells and their close surroundings in muscle biopsies of DM and PM patients but only in those areas of tissue sections where inflammatory cell infiltrates were present. No 3NT positivity was found in tissue sections of IIM patients without inflammatory infiltrates in the studied sample as well as in muscle tissue sections of patients with non-inflammatory myopathies. However, the endothelial cells were also positive in cases of confirmed non-inflammatory myopathies with secondary lymphocytic infiltration (myodystrophies, myasthenia gravis). Despite the pathogenetic significance, the 3NT immunohistochemistry is of low diagnostic value for the differential diagnosis of IIM in muscle biopsy.
Keywords: polymyozitida; Myotonic Dystrophy; biopsie; idiopatické zánětlivé myopatie; dermatomyozitida; Outcome and Process Assessment, Health Care; Myositis; Nitric Oxide; myozitida; Endothelial Cells; Biopsy; Immunohistochemistry; tyrosin; dermatomyositida; polymyositida; výsledky a postupy - zhodnocení (zdravotní péče); Myasthenia Gravis; myotonická dystrofie; Humans; Dermatomyositis; Financing, Organized; statistika jako téma; Polymyositis; endoteliální buňky; myasthenia gravis; Tyrosine; financování organizované; Statistics as Topic; oxid dusnatý; lidé; myodystrofie; imunohistochemie